Answer

5
(1 star)

1

Answer

0
(0 stars)

0

CalculatorK
1 year ago

12 response - 0 helps
**Answer:**

y=6

**Step-by-step explanation:**

(((−6)(2))(9))(y)=7y−4+4−690

−108y=7y+−4+4+−690

−108y=(7y)+(−4+4+−690)

−108y=7y+−690

−108y=7y−690

Subtract 7y from both sides.

−108y−7y=7y−690−7y

−115y=−690

Step 3: Divide both sides by -115.

−115y -690

−115 -115

y=6

I hope this helped!! If so please mark brainliest and rate my answer <33

Hey there!

-6×2×9y = 7y-4+4-690

=> Let's solve your equation step-by-step.

(((−6)(2))(9))(y)=7y−4+4−690

Step 1: Simplify both sides of the equation.

(((−6)(2))(9))(y)=7y−4+4−690

−108y=7y+−4+4+−690

−108y=(7y)+(−4+4+−690)(Combine Like Terms)

−108y=7y+−690

−108y=7y−690

Step 2: Subtract 7y from both sides.

−108y−7y=7y−690−7y

−115y=−690

Step 3: Divide both sides by -115.

−115y/−115 = −690/−115

y=6

Answer:

y=6

Therefore, the value of y = 6